Gravity Tide and seasonal gravity variation at Ny-Alesund, Svalbard In Arctic - Sato, Tadahiro; Boy, Jean-Paul; Tamura, Yoshiaki; Matsumoto, Koji; Asari, Kazuyoshi; Plag, Hans-Peter; FRANCIS, Olivier (Journal of Geodynamics, 2006)
peer reviewed